2014
DOI: 10.1142/s179354581350034x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a comprehensive indicator to nondestructively analyze watermelon quality at different ripening stages

Abstract: Two nondestructive methods based on visible and near-infrared (VIS-NIR) spectroscopy and X-ray image have been used for the evaluation of watermelon quality. The prediction performance based on partial least squares (PLS) by di®use transmittance measurement (500-1010 nm) was evaluated for chemical quality attributes SSC (Rc ¼ 0:903; RMSEC ¼ 0:572% Brix; Rp ¼ 0:862; RMSEP ¼ 0:717% Brix; RPD ¼ 1:83), lycopene (Rc ¼ 0:845; RMSEC ¼ 0:266 mg/ 100 gFW; Rp ¼ 0:751; RMSEP ¼ 0:439 mg/100 gFW; RPD ¼ 1:13) and moisture (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It was shown that X‐ray CT scanning could be useful in monitoring the internal changes of peach fruits. Recently, Qi and others () analyzed watermelon TSS at different maturity stages based on X‐ray image and VIS‐NIR spectroscopy (500 to 1010 nm) with PCA‐PLS model. In that study (Qi and others ), the X‐ray calibration linear equations had been developed by extracting the appropriate gray threshold and the prediction model was evaluated with RnormalP2 of 0.865, RMSEP of 0.00717, and RPD of 1.83.…”
Section: Nondestructive Analytical Techniquesmentioning
confidence: 99%
“…It was shown that X‐ray CT scanning could be useful in monitoring the internal changes of peach fruits. Recently, Qi and others () analyzed watermelon TSS at different maturity stages based on X‐ray image and VIS‐NIR spectroscopy (500 to 1010 nm) with PCA‐PLS model. In that study (Qi and others ), the X‐ray calibration linear equations had been developed by extracting the appropriate gray threshold and the prediction model was evaluated with RnormalP2 of 0.865, RMSEP of 0.00717, and RPD of 1.83.…”
Section: Nondestructive Analytical Techniquesmentioning
confidence: 99%
“…5 Agricultural products are significantly different from industrial products because of the variation in size, color, shape, and concentration of the chemical component of interest, caused by varied ripening stages, cultivars, origins, seasons, or even orchards, as well as the shelf-life. [6][7][8][9] Such variations lead to differences in light-scattering properties of fruit, and subsequently, the effective optical depth in samples would additionally be changed, affecting model validation performance. Because of the different qualities of Fuji apples from two main production areas (Shandong and Gansu) in China, samples from both these areas were studied to enlarge the variance of the sample sets during chemical-data collection, and thereby improve the reliability of modeling results.…”
Section: Introductionmentioning
confidence: 99%
“…The use of near infrared (NIR) spectroscopy to measure the SSC of fruit has been investigated extensively during the last decade because it is a rapid, real-time, reliable and non-invasive technology compared with most instrumental techniques. [1][2][3] A wide variety of fruit have been studied, ranging from apples 4,5 to peaches, 6,7 pears, 8,9 mandarins, 10,11 mangoes 12,13 and watermelon, 14,15 among others.…”
Section: Introductionmentioning
confidence: 99%